Biology of Black Soldier Fly (Hermetia illucens) and Utilization of its Waste (Maggot Frass) for Plant Growth: A Literature Review - Idris, Muhammad; Rismayani, Dessy; Aulia, Annisa; Nopiyanti, Tita; Rahayu, Resti (Jurnal Biologi Tropis, 2024)
The utilization of maggot frass from Black Soldier Fly (BSF) larvae (Hermetia illucens Linneus, 1875) has garnered attention in the context of organic farming as a promising alternative to enhance plant growth and development. Maggot frass, a byproduct of the larval digestion process, is rich in essential nutrients such as nitrogen, phosphorus, potassium, and contains beneficial microorganisms for the soil. This study employs a literature review method. Literature sources were obtained from the Google Scholar database using keywords such as "maggot frass", "kasgot", "Black Soldier Fly", and "Hermetia illucens". The articles obtained were then analyzed to gather secondary data. The aim of this research is to explore the potential utilization of maggot frass from BSF larvae in enhancing plant growth and development in the context of organic farming. Research on the utilization of maggot frass has shown significant potential in improving soil fertility and increasing crop productivity. Furthermore, the use of BSF larvae in organic waste management can also significantly reduce waste volume while creating valuable resources for agriculture. By integrating the utilization of maggot frass into organic farming practices, it is hoped that a more sustainable and environmentally friendly agricultural system can be created in the future.